Structure of needs of patients with diabetes in orthopedic treatment - T. I. Dimcheva (Kazimierz Wielki University, 2018)
The aim consisted in studying of frequency of visits of the stomatologist by patients with diabetes and structures of their needs in a denture. Results of a research. Within 1 year of the dentist on orthopedic reception visited 380 patients. From them 18 people (4.74%) aged from 18 till 62 years had diabetes and needed prosthetics. Patients with type 2 diabetes asked for the orthopedic help more often and the majority (90%) needed removable prosthetics. Among patients with type 1 diabetes - in the majority it is young people - persons met total absence of teeth. Conclusion. All patients with diabetes need special approach to performing orthopedic treatment. The special plan considering carrying out full sanitation of an oral cavity before prosthetics, the choice of prosthetics of an optimum type and structural material has to be developed for them